A carbon-carbon hybrid - immobilizing carbon nanodots onto carbon nanotubes - Strauß, Volker; Margraf, Johannes; Clark, Timothy; Guldi, Dirk Michael (Chemical Science, 2015)
The thrust of this work is to integrate small and uniformly sized carbon nanodots (CNDs) with single-walled carbon nanotubes (SWCNT) of different diameters as electron donors and electron acceptors, respectively, and to test their synergetic interactions in terms of optoelectronic devices. CNDs (denoted pCNDs, where p indicates pressure) were prepared by pressure-controlled microwave decomposition of citric acid and urea. pCNDs were immobilized on single-walled carbon nanotubes by wrapping the latter with poly(4-vinylbenzyl trimethylamine) (PVBTA), which features positively charged ammonium groups in the backbone. Negatively charged surface groups on the CNDs lead to attractive electrostatic interactions. Ground state interactions between the CNDs and SWCNTs were confirmed by a full-fledged photophysical investigation based on steady-state and time-resolved techniques. As a complement, charge injection into the SWCNTs upon photoexcitation was investigated by ultra-short time-resolved spectroscopy.

A Molecular Placeholder Strategy To Access a Family of Transition-Metal-Functionalized Vanadium Oxide Clusters - Kastner, Katharina; Margraf, Johannes; Clark, Timothy; Streb, Carsten (Chemistry - A European Journal, 2014)
Systematic access to metal-functionalized polyoxometalates has thus far been limited to lacunary tungsten oxide and molybdenum oxide clusters. The first controlled, stepwise bottom-up assembly route to metal-functionalized molecular vanadium oxides is now presented. A di-vacant vanadate cluster with two metal binding sites, (DMA)(2)[V12O32Cl](3-) (DMA= dimethylammonium) is formed spontaneously in solution and characterized by single-crystal X-ray diffraction, ESI mass spectrometry, V-51 NMR spectroscopy, and elemental analyses. In the cluster, the metal binding sites are selectively blocked by hydrogen-bonded DMA placeholder cations. Reaction of the cluster with transition metals TM (Fe3+, Co2+, Cu2+, Zn2+) gives access to mono-functionalized vanadate clusters (DMA)[TM(L)V12O32Cl](n-) (L= ligand). Metal binding is accomplished by significant distortions of the vanadium oxide framework reminiscent of a pincer movement. Cluster stability under technologically relevant conditions in the solid-state and solution is demonstrated.
Keywords: functionalization; metal oxide clusters; polyoxometalates; polyoxovanadates; self-assembly

An unsymmetrical pentacene derivative with ambipolar behavior in organic thin-film transistors - Tykwinski, Rik; Etschel, Sebastian; Halik, Marcus; Jäger, Christof; Clark, Timothy; Margraf, Johannes; Waterloo, Andreas; Hampel, Frank; Yousefi Amin, Atefeh (Chemical Communications, 2013)
Three new unsymmetrical anthracenyl-pentacene derivatives have been synthesized, characterized using X-ray crystallography, and used as semiconductors in OTFTs. For one derivative, ambipolar charge carrier transport was observed with a hole mobility of 0.2 cm V s and an electron mobility of 0.03 cm V s. © 2013 The Royal Society of Chemistry.

Blending Through-Space and Through-Bond π-π-Coupling in [2,2']-Paracyclophane-oligophenylenevinylene Molecular Wires - Wielopolski, Mateusz; Molina-Ontoria, Agustin; Schubert, Christina; Margraf, Johannes; Krokos, Evangelos; Kirschner, Johannes; Gouloumis, Andreas; Clark, Timothy; Guldi, Dirk Michael; Martin, Nazario (Journal of the American Chemical Society, 2013)
A series of ZnP-pCp-oPPV-C60 conjugates covalently connected through [2,2′]-paracyclophane-oligophenylenevinylene (pCp-oPPV) bridges containing one, two, and three [2,2′]-paracyclophanes (pCps) has been prepared in multistep synthetic procedures involving Horner–Wadsworth–Emmons olefination reactions and/or Heck type Pd-catalyzed reactions. Molecular modeling suggests that charge transfer is effectively mediated by the pCp-oPPVs through a predominant hole-transfer mechanism. Photophysical investigation supports molecular modeling and reveals two major trends. On one hand, C60 excitation of 1, 2, and 3 leads exclusively to charge transfer between pCp and C60 to afford a ZnP-(pCp-oPPV)•+-C60•– radical ion pair state without giving rise to a subsequent charge shift to yield the ZnP•+-pCp-oPPV-C60•– radical ion pair state. On the other hand, ZnP excitation of 1, 2, and 3 results in a rather slow charge transfer between ZnP and C60, after which the ZnP•+-pCp-oPPV-C60•– radical ion pair state evolves. In temperature-dependent ZnP fluorescence experiments, which were performed in the temperature range from 273 to 338 K, two domains are discernible: low and high temperature behaviors. In the low temperature range (i.e., below 30 °C) the rate constants do not change, suggesting that a superexchange mechanism is the modus operandi. In the high temperature range (i.e., >30 °C) the rate constants increase. Moreover, we find rather strong distance dependence for 1 and 2 and weak distance dependence for 2 and 3. A damping factor of 0.145 Å–1 is derived for the former pair and 0.012 Å–1 for the latter.
EAM Import::2019-03-13

Carbon Nanodots: Supramolecular Electron Donor-Acceptor Hybrids Featuring Perylenediimides - Strauß, Volker; Margraf, Johannes; Dirian, Konstantin; Syrgiannis, Zois; Prato, Maurizio; Wessendorf, Cordula; Hirsch, Andreas; Clark, Timothy; Guldi, Dirk Michael (Angewandte Chemie International Edition, 2015)
We describe the formation of charge-transfer complexes that feature electron-donating carbon nanodots (CND) and electron-accepting perylenediimides (PDI). The functionalities of PDIs have been selected to complement those of CNDs in terms of electrostatic and -stacking interactions based on oppositely charged ionic head groups and extended -systems, respectively. Importantly, the contributions from electrostatic interactions were confirmed in reference experiments, in which stronger interactions were found for PDIs that feature positively rather than negatively charged head groups. The electronic interactions between the components in the ground and excited state were characterized in complementary absorption and fluorescence titration assays that suggest charge-transfer interactions in both states with binding constants on the order of 8x10(4)M(-1) (25Lg(-1)). Selective excitation of the two components in ultrafast pump probe experiments gave a 210ps lived charge-separated state.
Keywords: carbon nanodots; charge transfer; donor-acceptor compounds; perylenediimides; transient absorption

Carbon Nanodots: Toward a Comprehensive Understanding of Their Photoluminescence - Strauß, Volker; Margraf, Johannes; Dolle, Christian; Butz, Benjamin; Nacken, Thomas; Walter, Johannes; Bauer, Walter; Peukert, Wolfgang; Spiecker, Erdmann; Clark, Timothy; Guldi, Dirk Michael (Journal of the American Chemical Society, 2014)
We report the characterization of carbon nanodots (CNDs) synthesized under mild and controlled conditions, that is, in a microwave reactor. The CNDs thus synthesized exhibit homogeneous and narrowly dispersed optical properties. They are thus well suited as a testbed for studies of the photophysics of carbon-based nanoscopic emitters. In addition to steady-state investigations, time-correlated single-photon counting, fluorescence up-conversion, and transient pump probe absorption spectroscopy were used to elucidate the excited-state dynamics. Moreover, quenching the CND-based emission with electron donors or acceptors helped shed light on the nature of individual states. Density functional theory and semiempirical configuration-interaction calculations on model systems helped understand the fundamental structure-property relationships for this novel type of material.

Directional Charge-Carrier Transport in Oriented Benzodithiophene Covalent Organic Framework Thin Films - Medina, Dana D.; Petrus, Michiel L.; Jumabekov, Askhat N.; Margraf, Johannes; Weinberger, Simon; Rotter, Julian M.; Clark, Timothy; Bein, Thomas (Acs Nano, 2017)
Charge-carrier transport in oriented COF thin films is an important factor for realizing COF-based optoelectronic devices. We describe how highly oriented electron-donating benzodithiophene BDT-COF thin fihns serve as a model system for a directed charge-transport study. Oriented BDT-COF films were deposited on different electrodes with excellent control over film roughness and topology, allowing for high-quality electrode COF interfaces suitable for device fabrication. Hole only devices were constructed to study the columnar hole mobility of the BDT-COF films. The transport measurements reveal a clear dependency of the measured hole mobilities on the BDT-COF film thickness, where thinner films showed about two orders of magnitude higher mobilities than thicker ones. Transport measurements under illumination yielded an order of magnitude higher mobility than in the dark. In-plane electrical conductivity values of up to 5 X 10(-7) S cm(-1) were obtained for the oriented films. Impedance measurements of the hole-only devices provided further electrical description of the oriented BDT-COF films in terms of capacitance, recombination resistance, and dielectric constant. An exceptionally low dielectric constant value of approximately 1.7 was estimated for the BDT-COF films, a further indication of their highly porous nature. DFT and molecular-dynamics simulations were carried out to gain further insights into the relationships between the COF layer interactions, electronic structure, and the potential device performance.
Keywords: covalent organic frameworks; thin films; charge transport; hole mobility; electrical conductivity; impedance spectroscopy

EMPIRE: a highly parallel semiempirical molecular orbital program: 2: periodic boundary conditions - Margraf, Johannes; Hennemann, Matthias; Meyer, Bernd; Clark, Timothy (Journal of Molecular Modeling, 2015)
No abstract available for this article

From benzodithiophene to diethoxy-benzodithiophene covalent organic frameworks-structural investigations - Lohse, Maria S.; Rotter, Julian M.; Margraf, Johannes; Werner, Veronika; Becker, Matthias; Herbert, Simon; Knochel, Paul; Clark, Timothy; Bein, Thomas; Medina, Dana D. (Crystengcomm, 2016)

Integrating metalloporphycenes into p-type NiO-based dye-sensitized solar cells - Feihl, Sebastian; Costa, Ruben D.; Brenner, Wolfgang; Margraf, Johannes; Casillas Pacheco, Ruben; Langmar, Oliver; Browa, Anne; Shubina, Tatyana; Jux, Norbert; Guldi, Dirk Michael; Clark, Timothy (Chemical Communications, 2014)
In the current work, we have explored a novel synthetic route towards metalated porphycenes and their use in p-type NiO-based dye-sensitized solar cells. Particular emphasis is placed on the influence that the relative positioning of the anchoring group exerts on the DSSC performance.

Molecular docking sites designed for the generation of highly crystalline covalent organic frameworks - Ascherl, Laura; Sick, Torben; Margraf, Johannes; Lapidus, Saul H.; Calik, Mona; Hettstedt, Christina; Karaghiosoff, Konstantin; Doeblinger, Markus; Clark, Timothy; Chapman, Karena W.; Auras, Florian; Bein, Thomas (Nature Chemistry, 2016)
Covalent organic frameworks (COFs) formed by connecting multidentate organic building blocks through covalent bonds provide a platform for designing multifunctional porous materials with atomic precision. As they are promising materials for applications in optoelectronics, they would benefit from a maximum degree of long-range order within the framework, which has remained a major challenge. We have developed a synthetic concept to allow consecutive COF sheets to lock in position during crystal growth, and thus minimize the occurrence of stacking faults and dislocations. Hereby, the three-dimensional conformation of propeller-shaped molecular building units was used to generate well-defined periodic docking sites, which guided the attachment of successive building blocks that, in turn, promoted long-range order during COF formation. This approach enables us to achieve a very high crystallinity for a series of COFs that comprise tri- and tetradentate central building blocks. We expect this strategy to be transferable to a broad range of customized COFs.

Molecular wires - impact of π-conjugation and implementation of molecular bottlenecks - Schubert, Christina; Margraf, Johannes; Clark, Timothy; Guldi, Dirk Michael (Chemical Society Reviews, 2015)
In this review we highlight recent progress in the field of photochemically and thermally induced electron transport through molecular bridges as integrative parts of electron donor-bridge-acceptor conjugates. The major emphasis is hereby on the design and the modular composition of the bridges. To this end, we will demonstrate that control over attenuation factors and reorganization energies, on one hand, as well as electronic and electron-vibration couplings, on the other hand, enables tuning electron transport over distances as short as 3.5 Å and as large as 50 Å by up to nine orders of magnitude. In terms of electron transport, the maximum extreme is given by carbon-bridged oligo-p-phenylenevinylenes of different lengths, while a zinc tetraphenylporphyrin free base tetraphenylporphyrin dyad constitutes the minimum extreme.
EAM Import::2019-03-12

P-doped multiwall carbon nanotube/perylene diimide derivative photoelectrochemical cells for photocurrent generation - Troeger, Anna; Ledendecker, Marc; Margraf, Johannes; Sgobba, Vito; Guldi, Dirk Michael; Vieweg, Benito; Spiecker, Erdmann; Suraru, Sabin-Lucian; Wuerthner, Frank (Advanced Energy Materials, 2012)
A perylene diimide (PDI) derivative bearing four chlorine substituents in the bay area is deposited together with pristine multiwall carbon nanotubes (MWNTs) and/or Nafion p-doped MWNTs (p-MWNTs) onto indium tin oxide (ITO) solid substrates by means of air-brushing. The resulting photoanodes are studied in photoelectrochemical cells and reveal highest photocurrent efficiencies when PDI and p-MWNT are combined as photoactive materials, indicating the beneficial effect of Nafion.

Quantum-dot-sensitized solar cells: Understanding linker molecules through theory and experiment - Margraf, Johannes; Ruland, Andres; Sgobba, Vito; Guldi, Dirk Michael; Clark, Timothy (Langmuir, 2013)
We have investigated the role of linker molecules in quantum-dot-sensitized solar cells (QDSSCs) using density-functional theory (DFT) and experiments. Linkers not only govern the number of attached QDs but also influence charge separation, recombination, and transport. Understanding their behavior is therefore not straightforward. DFT calculations show that mercaptopropionic acid (MPA) and cysteine (Cys) exhibit characteristic binding configurations on TiO2 surfaces. This information is used to optimize the cell assembly process, yielding Cys-based cells that significantly outperform MPA cells, and reach power conversion efficiencies (PCE) as high as 2.7% under AM 1.5 illumination. Importantly, the structural information from theory also helps understand the cause for this improved performance.

Screening Supramolecular Interactions between Carbon Nanodots and Porphyrins - Cadranel, Alejandro; Strauß, Volker; Margraf, Johannes; Winterfeld, Kim; Vogl, Christoph; Dordevic, Luka; Arcudi, Francesca; Hölzel, Helen; Jux, Norbert; Prato, Maurizio; Guldi, Dirk Michael (Journal of the American Chemical Society, 2018)
We present an in-depth investigation regarding the electron-accepting nature of pressure-synthesized carbon nanodots (pCNDs) in combination with porphyrins as excited-state electron donors. To this end, electrostatic attractions involving negative charges, which are present on the pCND surface, are essential to govern the hybrid assembly, on one hand, and charge separation, on the other hand.
CRIS-Team Scopus Importer:2022-04-14

Synchronized Offset Stacking: A Concept for Growing Large-Domain and Highly Crystalline 2D Covalent Organic Frameworks - Auras, Florian; Ascherl, Laura; Haldmioun, Amir H.; Margraf, Johannes; Hanusch, Fabian C.; Reuter, Stephan; Bessinger, Derya; Doeblinger, Markus; Hettstedt, Christina; Karaghiosoff, Konstantin; Herbert, Simon; Knochel, Paul; et al. (Journal of the American Chemical Society, 2016)
Covalent organic frameworks (COFs), formed by reversible condensation of rigid organic building blocks, are crystalline and porous materials of great potential for catalysis and organic electronics. Particularly with a view of organic electronics, achieving a maximum degree of crystallinity and large domain sizes while allowing for a tightly pi-stacked topology would be highly desirable. We present a design concept that uses the 3D geometry of the building blocks to generate a lattice of uniquely defined docking sites for the attachment of consecutive layers, thus allowing us to achieve a greatly improved degree of order within a given average number of attachment and detachment cycles during COF growth. Synchronization of the molecular geometry across several hundred nanometers promotes the growth of highly crystalline frameworks with unprecedented Spectroscopic data indicate considerable delocalization of excitations along the pi-stacked columns and the feasibility of donor-acceptor excitations across the imine bonds. The frameworks developed in this study can serve as a blueprint for the design of a broad range of tailor-made 2D COFs with extended pi-conjugated building blocks for applications in photocatalysis and optoelectronics.

Template-Dependent Photochemical Reactivity of Molecular Metal Oxides - Tucher, Johannes; Peuntinger, Katrin; Margraf, Johannes; Clark, Timothy; Guldi, Dirk Michael; Streb, Carsten (Chemistry - A European Journal, 2015)
A combined experimental and theoretical study shows that the photooxidative activity of two isostructural metal oxide clusters depends on their internal templates. To this end, two halide-templated bismuth vanadium oxide clusters [X(Bi(dmso)(3))(2)V12O33](-) (X=Cl-, Br-) are reported and fully characterized. The two clusters show similar absorption features and illustrate that bismuth incorporation results in increased visible-light absorption. Significantly higher photooxidative activity is observed for the bromide-templated cluster compared with the chloride-templated one. Detailed photophysical assays and complementary DFT calculations suggest that the more efficient triplet excited state formation in the Br–containing cluster is the decisive step in the photocatalysis and is due to the heavy-atom effect of the bromide. This concept can therefore open new pathways towards the optimization of photocatalytic activity in metal oxide clusters.
Keywords: density functional calculations; metal oxide; polyoxometalate; self-assembly; template

The Electronic Structure of Amorphous Carbon Nanodots - Margraf, Johannes; Strauß, Volker; Guldi, Dirk Michael; Clark, Timothy (Journal of Physical Chemistry B, 2015)
We have studied hydrogen-passivated amorphous carbon nanostructures with semiempirical molecular orbital theory in order to provide an understanding of the factors that affect their electronic properties. Amorphous structures were first constructed using periodic calculations in a melt/quench protocol. Pure periodic amorphous carbon structures and their counterparts doped with nitrogen and/or oxygen feature large electronic band gaps. Surprisingly, descriptors such as the elemental composition and the number of sp3-atoms only influence the electronic structure weakly. Instead, the exact topology of the sp2-network in terms of effective conjugation defines the band gap. Amorphous carbon nanodots of different structures and sizes were cut out of the periodic structures. Our calculations predict the occurrence of localized electronic surface states, which give rise to interesting effects such as amphoteric reactivity and predicted optical band gaps in the near-UV/visible range. Optical and electronic gaps display a dependence on particle size similar to that of inorganic colloidal quantum dots.

Theoretical and experimental insights into the surface chemistry of semiconductor quantum dots - Margraf, Johannes; Ruland Palaia, Andres; Sgobba, Vito; Guldi, Dirk Michael; Clark, Timothy (Langmuir, 2013)
We present a series of non-stoichiometric cadmium sulfide quantum-dot (QD) models. Using density functional theory (DFT) and semi-empirical molecular orbital (MO) calculations, we explore the ligand binding and exchange chemistry of these models. Their surface morphology allows for these processes to be rationalized on the atomic scale. This is corroborated by ultraviolet-visible (UV-vis), infrared (IR), and inductively coupled plasma-optical emission spectroscopy (ICP-OES). © 2013 American Chemical Society.

Thermochromic and solvatochromic properties of Lindqvist polyoxometalates - Herrmann, Sven; Margraf, Johannes; Clark, Timothy; Streb, Carsten (Chemical Communications, 2015)
The thermochromic and solvatochromic properties of Lindqvist metal oxide clusters [VxM6-xO19](n-) (x = 0, 1, 2, M = Mo, W) are reported. The cluster anions show pronounced changes of their electronic structure depending on their chemical environment (e.g. solvent polarity, temperature). These are rationalized using experimental and theoretical methods. A combined density functional theory and V-51-NMR study suggests that temperature-dependent changes in the structural dynamics of the metal oxide framework are the underlying cause for the observed thermochromism. The results might open new avenues for the design of molecular optical sensors.

Tuning the reorganization energy of electron transfer in supramolecular ensembles - metalloporphyrin, oligophenylenevinylenes, and fullerene - and the impact on electron transfer kinetics - Stangel, Christina; Schubert, Christina; Kuhri, Susanne; Rotas, Georgios; Margraf, Johannes; Regulska, Elzbieta; Clark, Timothy; Torres, Tomas; Tagmatarchis, Nikos; Coutsolelos, Athanassios G.; Guldi, Dirk Michael (Nanoscale, 2015)
Oligo(p-phenylenevinylene) (oPPV) wires of various lengths featuring pyridyls at one terminal and C-60 moieties at the other, have been used as molecular building blocks in combination with porphyrins to construct a novel class of electron donor-acceptor architectures. These architectures, which are based on non-covalent, directional interactions between the zinc centers of the porphyrins and the pyridyls, have been characterized by nuclear magnetic resonance spectroscopy and mass spectrometry. Complementary physico-chemical assays focused on the interactions between electron donors and acceptors in the ground and excited states. No appreciable electron interactions were noted in the ground state, which was being probed by electrochemistry, absorption spectroscopy, etc.; the electron acceptors are sufficiently decoupled from the electron donors. In the excited state, a different picture evolved. In particular, steady-state and time-resolved fluorescence and transient absorption measurements revealed substantial electron donor-acceptor interactions. These led, upon photoexcitation of the porphyrins, to tunable intramolecular electron-transfer processes, that is, the oxidation of porphyrin and the reduction of C-60. In this regard, the largest impact stems from a rather strong distance dependence of the total reorganization energy in stark contrast to the distance independence seen for covalently linked conjugates.

Using carbon nanodots as inexpensive and environmentally friendly sensitizers in mesoscopic solar cells - Margraf, Johannes; Lodermeyer, Fabian; Strauß, Volker; Haines, Philipp; Walter, Johannes; Peukert, Wolfgang; Costa, Ruben Dario; Clark, Timothy; Guldi, Dirk Michael (Nanoscale Horizons, 2016)
We discuss the use of carbon nanodots (CNDs) as sensitizers in mesoscopic solar cells. The CNDs are synthesized using a one-step, bottom-up microwave approach with citric acid, urea, and formic acid as precursors in aqueous media. Their light-harvesting capabilities can be tuned by adjusting the synthetic parameters. Comprehensive spectroscopic and theoretical studies allow us to rationalize the nature of their absorption features. Promising power conversion efficiencies ( extgreekh) of 0.24% can be achieved from these cheap and eco-friendly sensitizers by optimizing the solar-cell assembly process. Interestingly, we found that extending the light absorption towards longer wavelengths does not necessarily improve the performance of the solar cells, since the longer-wavelength absorption features hardly contribute to the cells' photo-action spectra, so that the overall power conversion efficiency is actually worse. The origin of the lower performance is corroborated in transient absorption spectroscopy and photovoltage decay measurements. Our work points, on one hand, to the limits of as-synthesized CNDs as photosensitizers and, on the other hand, to possible improvements.